Membangun Generasi Sehat dan Bugar Melalui Gerak dan Olahraga - Tasni Frikansi, Lucky Alam Apiyansyah, Rahmat, Sukma Qirani, Helni, Suryani (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
This study aims to explore the role of movement and sport in building a healthy and fit generation at SMP N 1 Kendari, Southeast Sulawesi. Using a descriptive qualitative approach, this study collected data through interviews, observations and literature studies to gain an in-depth understanding of students' experiences with healthy and fit movement and the role of sport in their daily lives. The results showed that the integration of movement and sport in the education curriculum has a significant positive impact on students' physical, mental, social and emotional health. Regular physical activity helps to improve physical fitness, reduce stress and improve students' concentration at school. In addition, sport also plays an important role in building students' social skills and self-confidence through participation in group and competitive activities. Strategies to strengthen movement and sports programs include education on the benefits of sports, social campaigns to raise public awareness, policies that support the accessibility of sports facilities, and collaboration between the public and private sectors. Thus, this study suggests that holistic implementation of movement and sport can be an effective solution in building a healthier and fitter generation in Indonesia.